Pengelolaan digital PR melalui Website ppid.kai.id - Safarizki, Dio Ahmad; Fakhruroji, Moch.; Risdayah, Enok (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2020)
This research was conducted with the aim of how to manage digital PR on the ppid.kai.id website through the four steps public relations concept initiated by Cutlip, Center, and Broom. This research was carried out using a qualitative descriptive method with primary and secondary data through data collection techniques, namely in-depth interviews, observation, and documentation studies. The results obtained are that the PPID KAI public relations unit is appropriate in carrying out digital PR management through the website ppid.kai.id in line with the four steps public relations concept, with the following indicators: 1) fact finding: searching and collecting data through requests for information as data. primary and work unit data as secondary data sources; 2) planning and programming: introduction of the PPID website to the public, internal PPID meetings, coordination meetings of the KAI work unit, and coordination meetings with the IT team; 3) taking action and communicating: managing information offline and online 4) evaluating the program: external satisfaction survey, internal evaluation, and evaluation of the central information commission.